ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI KERIPIK UBI (STUDI KASUS PADA USAHA KERIPIK KAK CUT NASABE DI GAMPONG SUAK RAYA KECAMATAN JOHAN PAHLAWAN KABUPATEN ACEH BARAT) - Irvan Novizar; Said Mahjali; Agustiar Agustiar (Universitas Teuku Umar, 2018)
This study was conducted at Kak Cut Nasabe Chips busines which is located in the Village of Suak Raya Johan Pahlawan Aceh barat district. The purpose of the research to analyze the factors that affecting the production of potato chips by using cobb douglas production function. The Variables used is consist of labor and raw materials factor. The cooefisien value of determination (R2) obtained is 0.980, this means that the diversity of potato chips production variables can be explained by the variable labor and raw materials is 98% and 2% remaining is influenced by outside factors that is not studied